Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3389/fmicb.2020.00894
|View full text |Cite
|
Sign up to set email alerts
|

Exopolysaccharides From Streptococcus thermophilus ST538 Modulate the Antiviral Innate Immune Response in Porcine Intestinal Epitheliocytes

Abstract: Exopolysaccharide-Mediated Antiviral Immunomodulation milks obtained from S. thermophilus epsB and epsC. These results suggest that S. thermophilus ST538 could be used as an immunobiotic strain for the development of new immunologically functional foods, which might contribute to improve resistance against viral infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 55 publications
1
17
0
Order By: Relevance
“…Piglets with high intestinal concentrations of S. suis can serve as a source of transmission and infection between animals and farms (reviewed in [ 39 ]). In general Streptococcus are less abundant in more-feed efficient pigs [ 37 ], although there are also evidences of the immunomodulatory properties of members of Streptococcus genus, such as Streptococcus thermophilus , considered beneficial for the organism [ 40 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Piglets with high intestinal concentrations of S. suis can serve as a source of transmission and infection between animals and farms (reviewed in [ 39 ]). In general Streptococcus are less abundant in more-feed efficient pigs [ 37 ], although there are also evidences of the immunomodulatory properties of members of Streptococcus genus, such as Streptococcus thermophilus , considered beneficial for the organism [ 40 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, an EPS produced by Lactobacillus delbrueckii OLL1073R-1 activated the Toll-like receptor 3 (TLR3) and the expression of interferon (IFN)-α, IFN-β, MxA, and RNase L in porcine intestinal epithelial (PIE) cells, which was associated with the innate antiviral immune response (77). Mizuno et al (98) reported that an EPS from Streptococcus thermophilus ST538 can activate TLR3, thus promoting the expression of IFN-β, interleukin 6 (IL-6), and C-X-C motif chemokine 10 (CXCL10). Antiviral bacterial polysaccharides are also shown in Table 1.…”
Section: Antiviral Polysaccharides From Bacteriamentioning
confidence: 99%
“…For example, an EPS extracted from S. thermophilus ST538 was able to induce the expression of IFNβ, IL-6, and CXCL10 in response to TLR3 stimulation. These immune factors are associated with antiviral immune responses, which induce the recruitment and activation of immune cells to struggle pathogens (98). Moreover, L. delbrueckii OLL1073R-1 produced immunomodulatory EPS.…”
Section: Modulating Host Antiviral Immune Responsesmentioning
confidence: 99%
“…Structurally, the repeating units of the EPSs from LAB might be linear or highly branched, with the molecular weight (Mw) of the EPSs up to about 10 6 Da [3]. These EPSs have been shown to possess various bioactivities, such as antitumor [4], immunomodulation, interfering with adhesion of pathogens, inhibiting proliferation of the human colon cancer cell line, and improving resistance against viral infections [5].…”
Section: Introductionmentioning
confidence: 99%